Effect of methyl jasmonate on physico-chemical properties of mango (Mangifera indica) fruits cv Dashehari during cold storage - KILLADI, BHARATI; LENKA, JOTIRMAYEE; CHAURASIA, REKHA; SHUKLA, D K (The Indian Journal of Agricultural Sciences, 2018)
Mango (Mangifera indica L.) fruits are climacteric in nature and have a very limited shelf-life thereby it is a challenge for prolonged storage. Use of cold storage is alternative approach to enhance the shelf-life of mango. Therefore, an integrated approach for shelf-life extension of fruits is done by pre-treatment with safe chemicals and storage at low temperature. Mature fruits of mango Dashehari were treated with hot water (52±2oC), methyl jasmonate (0.01%), methyl salicylic acid and control (normal tap water) for 3 minutes and stored at low temperature (12±2oC and 85 to 90 % RH). Fruits were withdrawn at weekly interval and assessed for physico-chemical parameters. The cumulative physiological loss in weight (CPLW) was 10.26 per cent in control fruits, while it was 5.12% in fruits treated with methyl jasmonate on 28 day of storage. The CPLW were 13.95 and 8.64% for control and methyl jasmonate treated fruits, respectively on 28+3 days under ambient conditions. The TSS:acid ratio in untreated fruits was 7.39, whereas treated fruits had 7.65 on 28 day of storage. The acidity of the fruits decreased with increase in storage. Total carotenoids content of the treated and control fruits on 28 day of storage were 2.42 and 1.44 mg/100g, respectively. The fruits of mango cv Dashehari on the day of harvest had antioxidant content of 0.54 mili moles trolox equivalent, while it was 2.57 mili moles trolox equivalent compared to control on the 21 day of storage under cold storage (12±2 oC and 85 to 90 % RH). Conclusively methyl jasmonate 0.01% treated fruits of Dashehari could be stored for 28 plus 3 days than normal shelf-life of 21 days under cold storage (12±2o C and 85-90% RH).